Analisis Kinerja Keuangan Bank Perkreditan Rakyat (BPR) di Wilayah Provinsi Jawa Barat - Zsa Zsa Juventia; Rofina Amelia; Hartantri Setiasih; Suripto Suripto (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This research aims to determine, identify and evaluate the financial performance of Rural Banks (BPR) operating in West Java Province in 2024. This research uses a quantitative descriptive statistical method with secondary data obtained from the official website of the Financial Services Authority (OJK). The data consist of quarterly financial statements of BPRs in West Java for 2024, with 76 out of 87 BPRs publishing their reports. Bank performance is analyzed using the CAMEL approach, which includes capital, asset quality, profitability, and liquidity. Capital is measured by the Capital Adequacy Ratio (CAR), asset quality by the Non-Performing Loan (NPL) ratio, profitability by Return on Assets (ROA) and the BOPO ratio, and liquidity by the Cash Ratio. The result show that 76 BPRs in West Java were in a stable condition in terms of capital and liquidity. However, 9 BPRs had weak asset quality, 1 BPR showed low ROA, and 3 BPRs had BOPO values indicating that efficiency still needs improvement.